Deelnemende aksie-navorsing as model vir benutting deur gesondheidswetenskaplikes - Strydom, H (Social Work/Maatskaplike Werk, 2001)
In Participatory Action Research the focus is on the involvement and participation of all the role players in the particular research project. Up to this stage uncertainty exists about the relationship between community development and the PAR model. Eventually in this model the process of community work and the research process takes hands and the boundaries between them become vague. PAR is widely endorsed as consistent with health professionals' commitment to social justice - PAR promises to connect local action to large-scale, progressive social change. The researcher remains responsible for the research process and the community worker should act on the recommendations of the researcher in order to improve the quality of life in the particular community. In this article the appropriate terminology has been defined, the characteristics, the process and the data-collection techniques of the PAR model identified and the advantages and disadvantages of the model evaluated.